Pilgrimage Notes. Religious Tourism and Ethnosemiotics - Galofaro, Francesco (E|C, 2022)
During its development, semiotics has mainly dealt with documents, whose meaning is reconstructed starting from a support which can be archived: volumes, films, CDs, databases, music scores. However, in the perspective of Greimas and his school, the text should not be confused with the document, since the former is the result of an analysis applied to a signifying set. Thus, at least since the late 1990s, semiotics has become interested in objects of study that are not ready-made documents: practices, rituals, spaces that contain them, events that happen under the eyes of the observer, and whose analysis should be considered the application of a semiotechnique, aimed at the production of meaning. This leads to the main question around which ethnosemiotics revolves: what are the conditions of possibility of ethnographic inquiry? The present work tries to answer the question starting from a case study: a pilgrimage to the shrine of Koden which I participated in on August 15, 2021, on the occasion of the celebrations for the assumption of Mary.